A Comparative Study of Cooltech® Handpieces for Cryoadipolysis Using Numerical Simulation - Viera-Mármol, Gregorio; Villena, Jorge; García, Pablo; Khrystova, Kristina; Colina, Mónica (Problems of Cryobiology and Cryomedicine, 2019)
Cryoadipolysis is a non-invasive procedure that results in a significant reduction of localized subcutaneous fat. The purpose of the study was to compare the cooling dynamics of Cooltech® handpieces analysing simulations of their performance and operational efficiency with Comsol Multiphysics®. All handpieces showed a timebased decreasing tendency in temperature. The central zone of all showed a similar response, except the handpiece that can lodge smaller volume of fat. The greater the volumetric capacity of fat, the less homogeneous was the temperature distribution, and the handpieces needed more time to reach the target temperatures. The widest handpiece reached a lower percentage of fat (69.06%) below the crystallization temperatures, and the handpiece that can lodge the larger volume of all tested, reached 81.93%. Numerical simulations, and particularly the model applied, are a very useful tool to optimize treatment time and improve the designs and therapeutic efficacy of handpieces. Probl Cryobiol Cryomed 2018; 28(4): 343-356